Elevated serum substance P during simian varicella virus infection in rhesus macaques; implications for chronic inflammation and adverse cerebrovascular events - Bubak, Andrew N. (J Neurovirol, 2020)
Varicella and zoster, produced by varicella zoster virus (VZV), are associated with an increased risk of stroke that may be due to persistent inflammation and hypercoagulability. Because substance P is associated with inflammation, hypercoagulability, and atherosclerotic plaque rupture that may contribute to increased stroke risk after VZV infection, we measured serum substance P in simian varicella virus-infected rhesus macaques. We found significantly increased and persistent serum substance P concentrations during varicella and zoster compared to pre-inoculation, supporting the hypothesis that VZV-induced increases in serum substance P may contribute to increased stroke risk associated with VZV infection.